2017
DOI: 10.1055/s-0042-121575
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitrectomy Combined with Subretinal rtPA Injection with Gas or Air Tamponade

Abstract: Functional and anatomical outcome after vitrectomy with rtPA combined with gas or air tamponade. Retrospective analysis of pseudophakic patients treated with subretinal rtPA and gas or air tamponade. The primary endpoint was displacement of haemorrhage six months after surgery. The secondary endpoints were visual acuity (BCVA), haemorrhage diameter (MHD) and central macular thickness (CMT), as measured by SD-OCT. 53 of 85 eyes were pseudophakic. 27 of these eyes were treated with air tamponade and 26 with gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…This procedure reduces the risk of iatrogenic RD and PVR and causes less damage to the photoreceptors during clot removal [24]. When further combined with gas, vitrectomy and subretinal TPA administration avoids the mechanical removal of the clot [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure reduces the risk of iatrogenic RD and PVR and causes less damage to the photoreceptors during clot removal [24]. When further combined with gas, vitrectomy and subretinal TPA administration avoids the mechanical removal of the clot [9].…”
Section: Discussionmentioning
confidence: 99%
“…rTPA dissolves the SMH and the gas displaces the SMH by either steam roller action or by gravity to a region where the SMH can be reabsorbed and the damage caused by SMH can be reduced [8]. It is been also shown that an air tamponade is as effective as gas, indicating that the duration of blood displacement is not a key factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this retrospective case series study group 2 we used 20% sulphur hexafluoride as a tamponade and added subretinal air as pneumatic subretinal displacement of the SMH in the subgroup 2A. Waizel M. et al in his retrospective analysis of 85 pseudophakic patients had undergone PPV +subretinal tPA and air or gas tamponade with 64.1% complete displacement of SMH away from fovea, highlighted that patients who had air as a tamponade achieved final visual acuity better than others who had gas tamponade either SF6 or C2F6 despite of similar anatomical outcome in the two groups 11 . The displacement rate is 100% in our series probably due to early intervention in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Sub foveal large haemorrhages carries poor prognosis 3 . A few surgical techniques were described to treat SMH 4,5,6,7,8,9,10,11,12,13 . In this study we analysed the outcome of two commonly used methods;…”
Section: Introductionmentioning
confidence: 99%
“…Sub foveal large haemorrhages carries poor prognosis 3 . A few surgical techniques were described to treat SMH 4,5,6,7,8,9,10,11,12,13 . In this study we analysed the outcome of two commonly used methods; Intravitreal gas and TPA versus PPV, Subretinal TPA and gas.…”
Section: Introductionmentioning
confidence: 99%